The Effects of Inoculation with Pseudomonads Rhizobacteria on Growth, Quantity and Quality of Essential Oils in Sage (Salvia officinalis L.) Plant - M Ghorbanpour; N Hosseini; M Khodae Motlagh; M Solgi (Institue of Medicinal Plants, ACECR, 2014)
Background: rhizobacteria are specific group of soil microorganisms that aggressively colonize the rhizosphere and rhizoplane, and substantially improve plant growth and efficiency via direct or indirect mechanisms. Objective: To investigate the growth promoting effects of rhizobacteria strains on cuttings growth and variations of essential oils content and yield in Salvia officinalis. Methods: In this research, different rhizobacteria including Pseudomonas putida (strains 41 and 159) and fluorescence (strain 23) with different growth promoting characteristics was used first on stem cuttings and later on aerial parts of S. officinalis L. (with final concentration of 109 CFU/ml). The essential oils were isolated from aerial parts of the plants by hydro-distillation method and then subjected to GC and GC-MS apparatus to determine the oil constituents. Results: Results showed that the dry weight of above and below ground parts of plants were increased in response to employed rhizobacteria inoculation. The highest root and leaf dry weight were observed in plants treated with Putida strain 159 which is caused increase of 45% and 33% compared to control untreated plants, respectively. Also, the highest essential oil yield was obtained in plants treated with putida strains, and the lowest of that was gained in control plants and also plants treated with fluorescence strain. The most abundant essential oil components were cis-Thujone, camphor, 1,8-cineol, camphene, α-pinene, viridiflorol, α-humulene, borneol and trans-meta-mentha-2 ,8-diene. Conclusion: Results from the current research indicate the plants inoculation with rhizobacteria had positive impact only on the major constituents of the essential oil compared to controls.